MANAJEMEN RISIKO STRATEGIS DALAM PERBANKAN SYARIAH: PENDEKATAN INTEGRATIF TERHADAP KETIDAKPASTIAN EKSTERNAL DAN KEPATUHAN SYARIAH - Dewi Aulia Sari; Putri Handayani; Rangga Putra Andika (PT. Hasba Edukasi Mandiri, 2025)
Strategic risk management is a crucial element in ensuring the sustainability of Islamic banking institutions, which operate in an environment full of uncertainty and bound by Sharia principles. This study aims to identify strategic risk management practices in national Islamic commercial banks and evaluate the integration between long-term business strategies and compliance with Sharia regulations. Through a descriptive qualitative approach involving literature studies and in-depth interviews, the findings reveal that Islamic banks face strategic risks arising from regulatory changes, competitive dynamics, and the expectations of Sharia stakeholders. The results show that institutions that proactively implement strategic risk management are better able to maintain stability and uphold their Sharia reputation.